The Typical Writing of Discussion Paragraph in Scientific Articles - Salem, Anwar Abbas; Salem, Muna Abbas; Mohamed, Aamer S.; Shiba, Omar A. (Wadi Alshatti University Journal of Pure and Applied Sciences, 2025)
Writing the part describing and discussing the results of the study is no less difficult than writing the article itself, and may even be more difficult, as in the best studies, the author may fail to convince the reviewers or evaluators if the results of this study are not explained well. And justify it with evidence. In many cases, poor discussion of the results leads to the rejection of the entire article, so this study will highlight the importance of this part and what is related to it, and try to direct the author to use the optimal methods for writing this part, as the stages or paragraphs that this part will contain will be determined, which are: In three paragraphs, which are the introductory paragraph, the middle paragraph, and the concluding paragraph, then directing the author to what he can be sure to include in this part and what he can avoid, then we conclude this study with a set of recommendations that may help the author in Writing this important part of his study.